The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/lnc3.12155
|View full text |Cite
|
Sign up to set email alerts
|

Language Policies, Ideologies, and Attitudes, Part 2: International Immigration, Globalization and the Future of Catalan

Abstract: This, the second of two articles on Catalonian language policies and their sociolinguistic effects, reviews research related to the current policy called the Pla per la Llengua i la Cohesió Social (Plan for Language and Social Cohesion) inaugurated in 2004. The Plan addresses a situation in which Catalan is stable demolinguistically but in which globalization and international immigration are seen as long‐term threats to the language's vitality. In addition, language planners were and remain concerned with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
(47 reference statements)
1
3
0
1
Order By: Relevance
“…There was, however, a clear age effect that permeated the two bilingual models, in the sense that the older students became the less often they used Basque in both contexts, even among model D students whose use of Basque significantly decreased from 79% to 44% in class and from 41% to 29% on the playground. These results concurred with those obtained in Catalonia (see Trenchs–Parera & Newman, ), where it was also observed that children whose language use was initially Catalan dominant tended to become increasingly bilingual, whereas those that showed a bilingual use or learned Catalan at school steadily moved toward an exclusive use of Spanish. Thus, it can be concluded that the influence of the use of the minority language as a means of instruction has a strong influence in the early stages of schooling, but its positive effect diminishes when students reach adolescence, a trend also detected in other European bilingual contexts such as Wales (Baker, ).…”
Section: The Connection Between Language Attitudes and Language Practsupporting
confidence: 90%
“…There was, however, a clear age effect that permeated the two bilingual models, in the sense that the older students became the less often they used Basque in both contexts, even among model D students whose use of Basque significantly decreased from 79% to 44% in class and from 41% to 29% on the playground. These results concurred with those obtained in Catalonia (see Trenchs–Parera & Newman, ), where it was also observed that children whose language use was initially Catalan dominant tended to become increasingly bilingual, whereas those that showed a bilingual use or learned Catalan at school steadily moved toward an exclusive use of Spanish. Thus, it can be concluded that the influence of the use of the minority language as a means of instruction has a strong influence in the early stages of schooling, but its positive effect diminishes when students reach adolescence, a trend also detected in other European bilingual contexts such as Wales (Baker, ).…”
Section: The Connection Between Language Attitudes and Language Practsupporting
confidence: 90%
“…In the late 1980s, Woolard made use of the label ‘new Catalans’ (: 44) to describe L2 Catalan speakers who come to adopt bilingual practices, seeing themselves as both Catalan and Spanish – a designation that, Woolard reports, very few native Catalonians would accept. More recently, Trenchs‐Parera and Newman (: 494) identify such attitudes to be associated with a broader cosmopolitanism, where younger middle‐class new speakers learn Catalan either for professional reasons, or as an academic exercise (see also Frekko, ). Similarly, Urla distinguishes between euskaldun zaharrak (‘old Basques’), who she describes as ‘native Basque speakers who tend to be primarily from farming and fishing communities’, and euskaldun berriak (‘new Basques’), comprised of ‘urban professionals, civil servants, and teachers who have mastered Standardised Basque’ (: 830) .…”
Section: On ‘New Speakers’mentioning
confidence: 99%
“…The negative attitudes manifested by most of the students seem to have roots in the perceived difficulty of learning Catalan -a challenge many of the newcomers did not expect before arriving. The surprise of encountering two official languages instead of only one has also been reported by other immigrant groups (Huguet, Janés & Chireac 2008;Madariaga, Huguet & Janés 2016;Trenchs-Parera & Newman 2015).…”
Section: Discussionmentioning
confidence: 62%